The Effects of a plyometric training program on maximal speed and Agility for soccer players “Category U19” - بلقاسم بوكراتم; مداني محمد (Journal of Sport Science Technology and Physical Activities, 2025)
The purpose of this study was to examine the effects of 6 weeks plyometric training program on maximal speed and agility for soccer players category U19. The subjects included 22, healthy, male from Cmb Arib , Division honor of Aindefla league of football. Participants devided into two groups. 11players in the experimental group and 11 players in the control group .The experimental group applied the six-week training program with 3 weekly sessions , while the control group applied the regular program with the team coach. The researchers used the Sprint 10m test and Illinois Agility Test. SPSS version 19 for Statistical Data Analysis. The results has shown that the plyometric training program is sufficient enough to have improvements on maximal speed and agility for soccer players